2015
DOI: 10.1007/s11894-015-0440-6
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for Patients with End-Stage Liver Disease

Abstract: Liver disease results in over four million physician visits and over 750,000 hospitalizations per year in the USA. Those with chronic liver disease frequently progress to cirrhosis, end-stage liver disease (ESLD), and death. Patients with ESLD experience numerous complications, including muscle cramps, confusion (hepatic encephalopathy), protein calorie malnutrition, muscle wasting, fluid overload (ascites, edema), bleeding (esophagogastric variceal hemorrhage), infection (spontaneous bacterial peritonitis), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 94 publications
(53 reference statements)
0
18
0
3
Order By: Relevance
“…Many people had multiple admissions during a single year (51%) and unplanned readmissions (36%), despite appropriate referrals for outpatient care: this is not accounted for by people having planned readmissions for paracentesis. Given that the more frequent the readmission rate, the greater the risk of subsequent mortality, targeting this group of people for specialist palliative care referral could enhance both quality of life and advance health planning rates.…”
Section: Discussionmentioning
confidence: 99%
“…Many people had multiple admissions during a single year (51%) and unplanned readmissions (36%), despite appropriate referrals for outpatient care: this is not accounted for by people having planned readmissions for paracentesis. Given that the more frequent the readmission rate, the greater the risk of subsequent mortality, targeting this group of people for specialist palliative care referral could enhance both quality of life and advance health planning rates.…”
Section: Discussionmentioning
confidence: 99%
“…If the patient is not a transplant candidate, consideration for destination TIPS or serial LVPs should be assessed as well as referral to palliative care services. Referral to palliative care for patients with advanced liver disease has been shown to objectively improve clinical and patient-reported outcomes and this service’s role in both transplant and non-transplant settings will need to be further explored [27,28]. Regardless, the development of ascites is a serious complication of advanced cirrhosis and portal hypertension, and reporting to the patient on their prognosis is critical.…”
Section: Ascitesmentioning
confidence: 99%
“…Despite increased attention paid to improving end-of-life care for patients with liver disease 6, 7 , little is known about the current quality of care, resources, and costs associated with treating these patients. A study using the Health and Retirement Survey found that patients with cirrhosis report worse health status and require more caregiver support compared to age-matched patients without cirrhosis, but the sample was limited to Medicare recipients and hospital illness experiences and costs were not detailed 8 .…”
Section: Introductionmentioning
confidence: 99%